Analisis Indeks Kepuasan Masyarakat Berdasarkan Nilai Unsur Pelayanan: Studi Kasus Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Aceh Timur - Dayat, Hidayatullah; Suherna, Fani (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2023)
This study aims to measure the Community Satisfaction Index (IKM)/ASN within the East Aceh District in 2022. IKM/ASN is used as an indicator to evaluate the quality of services provided by public service organization units to the community/ASN. The research method applies qualitative methods and has been tested and shows a confidence level of 95%, which indicates objectivity in measuring perceptions/respondents to public services. The results of the study provide answers that represent the perceptions of ASN/respondents in the East Aceh District Government on the quality of public services applied to the Personnel and Human Resources Development Board. In addition, the results of this study are also used as a benchmark in assessing the success of the one-door administration service program (integrated services) in an effort to accelerate the bureaucracy in the East Aceh District Government by obtaining a 2022 Community Satisfaction Index (IKM) value of 80.16, with a service quality category of